Corrosion stability of electrochemically deposited Zn-Mn coatings - Marija Riđošić (Journal of Engineering & Processing Management, 2017)
The topic of this paper is testing corrosion stability of electrodeposited Zn-Mn coatings by using electrochemical impedance spectroscopy (SEI). The coatings were deposited galvanostatically on a 3x3 cm steel. 99.99% pure zinc was used as the anode. The electrodeposition was carried out from four chloride solutions. Solution 1 was without manganese (3mol/dm 3 KCl, 0,42mol/dm 3 H 3 BO 3 , 0,45mol/dm 3 ZnCl ), solutions 2-4 had the same concentration of KCl, H 3 BO 3 and ZnCl 2 as in solution 1 and only MnCl 2 · 4H 2 O was added in various concentrations. Final concentrations of solutions 2-4 were as follows: solution 2 - [Mn 2+ ]:[Zn 2+ ]=1:1 (0,45mol/dm 3 MnCl 2 · 4H 2 O); solution 3-[Mn 2+ ]:[Zn 2+ ]=1:2 (0,225mol/dm 3 MnCl 2 · 4H 2 O,); solution 4-[Mn 2+ ]:[Zn 2+ ]=2:1 (0,9mol/dm 3 MnCl 2 · 4H 2 O). Zn-Mn coatings were electrodeposited on chemically prepared samples of steel (cathodes) for 15 minutes from all solutions at current densities of 1 А/dm 2 , 2 А/dm 2 and 4 А/dm 2 . The obtained results showed that the Zn-Mn coatings deposited at all current densities have a higher corrosion stability compared to the pure zinc coating. For examle, of all the coatings deposited at the current density of 1A/dm 2 the coating deposited from solution 2 had the greatest corrosion stability, whereas the coatings from solutions 3 and 4 were more corrosion resistant at the current density of 2 and 4A/dm 2 . Corrosion resistances, determined from the Nyquist diagrams (Zimag) of the pure Zn coatings, were in the range of 80-130 Ω, depending on the deposition current density, while the resistances of the alloy coatings were around 150-200 Ω. Based on results obtained by electrochemical impedance spectroscopy it can be concluded that the most resistant Zn-Mn coatings were deposited from the solution 3 ([Mn 2+ ]:[Zn2+]=1:2), at the current densities of 2 A/dm 2 and 4 A/dm 2.
Keywords: deposition current density; electrochemical deposition; electrochemical impedance spectroscopy; Zn-Mn coatings